2021
DOI: 10.3390/jpm11060532
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastatic Breast Cancer: How to Manage It?

Abstract: Breast cancer (BC) is the most frequent cancer among women and represents the second leading cause of cancer-specific death. A subset of patients with metastatic breast cancer (MBC) presents limited disease, termed ‘oligometastatic’ breast cancer (OMBC). The oligometastatic disease can be managed with different treatment strategies to achieve long-term remission and eventually cure. Several approaches are possible to cure the oligometastatic disease: locoregional treatments of the primary tumor and of all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…There is a subset of patients with metastatic breast cancer who present with limited disease, termed ‘oligometastatic’ breast cancer [ 67 ]. Oligometastatic breast cancer is defined as metastatic disease with limited spread and thus it may be possible to achieve longer survival in this select patient population [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a subset of patients with metastatic breast cancer who present with limited disease, termed ‘oligometastatic’ breast cancer [ 67 ]. Oligometastatic breast cancer is defined as metastatic disease with limited spread and thus it may be possible to achieve longer survival in this select patient population [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) and IMRT seem to be safe and associated with good outcomes. In several studies, patients with oligometastatic breast cancer and well-controlled primary were treated with SBRT targeting all metastatic sites, and progression-free survival ranged from 50% to 70% at two years [ 18 , 19 ]. The optimal ablative therapy for endobronchial oligometastases should ideally be decided in a multidisciplinary meeting including surgeons, radiation oncologists, and interventional radiologists’ input [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is very difficult to conduct a perfect random trial about the local therapy for primary stage IV breast cancer in a real world. Of particular note is oligometastatic disease, which can achieve long-term remission and even be cured through different treatment strategies ( 23 ). The BOMET MF14-01 study showed that bone metastasis only (especially oligometastatic bone and solitary bone) may take more advantage from local surgery ( 24 ).…”
Section: Discussionmentioning
confidence: 99%